Evaluating The General Perception of Soft skills On Employment Among Business Management Students: A Study of Shanker Dev Campus (People's Journal of Management, 2024)
Soft skills are increasingly recognized as essential for success in today's competitive job market, particularly within the field of business management. This research explores the general perception of soft skills on employment success among business management students, focusing on a Shanker Dev Campus. Using a simple random sampling approach, data was collected through questionnaire from a sample of students enrolled in business management programs at the campus.  Using descriptive analytical tools, Percentage, Mean, and Standard Deviation are calculated and quantitative analytical tools i.e. Correlation between perceived soft skills proficiency and employment success, prospects among students. Analysis of the data revealed insights into the perceived importance of soft skills such as communication, teamwork, and leadership, as well as their impact on students' preparedness for the workforce and career advancement opportunities. The findings highlight the need for targeted interventions to enhance the development of soft skills within business management education and better align curriculum with industry demands. This research contributes to a deeper understanding of the role of soft skills in shaping the career trajectories of business management students and provides valuable insights for educators, employers, and policymakers